2019
DOI: 10.1016/j.jid.2019.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing of ABCB5 Identifies Recurrent Melanoma Mutations that Result in Increased Proliferative and Invasive Capacities

Abstract: ABCB5 is an ABC transporter that was shown to confer low-level multidrug resistance in cancer. In this study, we show that ABCB5 was mutated in 13.75% of the 640 melanoma samples analyzed. Besides nonsense mutations, two mutation hotspots were found in the ABCB5 protein, in the drug-binding pocket and the nucleotide-binding domains. Four mutations, which are representative of the mutation pattern, were selected. ATPase assays showed that these mutations resulted in a decrease in basal ATP hydrolysis by ABCB5. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…ABCB5 is predominantly expressed in melanocytes and studies have indicated its involvement in tumor progression and resistance to various drugs in malignant tumors, including melanoma. [ 31 , 32 ] It affects the proliferative activity of melanoma cells and participates in VM. [ 33 ] Additionally, ABCB5 has been shown to promote tumor invasion by regulating EMT-related transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…ABCB5 is predominantly expressed in melanocytes and studies have indicated its involvement in tumor progression and resistance to various drugs in malignant tumors, including melanoma. [ 31 , 32 ] It affects the proliferative activity of melanoma cells and participates in VM. [ 33 ] Additionally, ABCB5 has been shown to promote tumor invasion by regulating EMT-related transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the role of these genes in the progression of GC and other cancers. Adenosine triphosphate ATP-binding cassette (ABCB5), as an ABC transporter, has shown linked to the development of drug resistance in many kinds of cancers, such as melanoma, human retinoblastoma, and acute leukemia [ 34 36 ]. Accumulating evidence revealed that the inhibition of ABCB5 had an impact on the malignant potential of cancer cells both in vitro and in vivo [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-PD-1 drugs such as pembrolizumab and nivolumab can achieve long-term survival for patients with metastatic melanoma [ 52 ]. PTEN , as a tumour suppressor gene [ 53 ], was found only in the normal class, suggesting that PTEN mutations may be a factor affecting immune properties. Therefore, we suggest that they are potential therapeutic targets to improve the immune response.…”
Section: Discussionmentioning
confidence: 99%